1989
DOI: 10.1083/jcb.109.6.2879
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies detect and stabilize conformational states of smooth muscle myosin.

Abstract: Abstract. Antibodies with epitopes near the heavy meromyosin/light meromyosin junction distinguish the folded from the extended conformational states of smooth muscle myosin. Antibody 10S.1 has 100-fold higher avidity for folded than for extended myosin, while antibody S2.2 binds preferentially to the extended state. The properties of these antibodies provide direct evidence that the conformation of the rod is different in the folded than the extended monomeric state, and suggest that this perturbation may ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…The specificity of antibody recognition has proven to be a useful tool for detecting and mapping the tertiary structure of many proteins, including, for example, myosin (32,81,89), creatine kinase (59), p53 (20,28,93), influenza RNA polymerase (79), and hepatitis C virus E2 glycoprotein (14,80). In this study, we found that several antibodies specific for the HSV ICP8 SSB can serve as immunochemical probes for the investigation of ICP8 topology during replication complex assembly.…”
Section: Discussionmentioning
confidence: 84%
“…The specificity of antibody recognition has proven to be a useful tool for detecting and mapping the tertiary structure of many proteins, including, for example, myosin (32,81,89), creatine kinase (59), p53 (20,28,93), influenza RNA polymerase (79), and hepatitis C virus E2 glycoprotein (14,80). In this study, we found that several antibodies specific for the HSV ICP8 SSB can serve as immunochemical probes for the investigation of ICP8 topology during replication complex assembly.…”
Section: Discussionmentioning
confidence: 84%
“…The required critical concentration increases dramatically when ATP is present in the solution (32) and decreases when the regulatory light chain of the myosin is phosphorylated (32,66). A short region near the carboxy terminus (tail end) of myosin has been shown to be crucial for filament self-assembly (33,63). Cross et al (9) proposed that a tail tip-to-tail tip association of two myosin molecules is responsible for forming an anti-parallel dimer, which then serves as a nucleation site for filament growth.…”
Section: Molecular Mechanism Of Thick Filament Assembly In Vitro and mentioning
confidence: 99%
“…Polyacrylamide SDS gels run on these supernatants confirmed the accuracy of the concentrations and indicated that the amount of contaminating actin was less than 5%. HMMs were anchored to the coverslip using antibody S2.2 (18), and actin filament movement was measured as described previously (16,19). The basic buffer typically used for actin treatment and washing in the flow cell (see below) contained 60 mM KCl, 25 mM imidazole-HCl (pH 7.4 at 30°C), 4 mM MgCl 2 , 1 mM EGTA, and 10 mM DTT (buffer A).…”
Section: Dna Engineering and Production Of Recombinant Baculoviruses-mentioning
confidence: 99%